HbA1c, coronary atheroma progression and cardiovascular events. (14th October 2021) - Dykun, I; Bayturan, O; Carlo, J; Nissen, S E; Nicholls, S J; Puri, R
Abstract: Background: Hemoglobin A1c (HbA1c) reflects long-term glycemic control and is associated with an increased risk of cardiovascular events among diabetic and non-diabetic patients. The specific impact of HbA1c upon atheroma progression and incident cardiovascular events relative to the presence of other cardiovascular risk factors remains uncertain. Purpose: We tested the hypothesis that on-treatment HbA1c levels independently associate with coronary atheroma progression measured with serial intravascular ultrasonography (IVUS) and major adverse cardiovascular events (MACE: death, myocardial infarction, cerebrovascular accident, coronary revascularization, or hospitalization for unstable angina) rates. Methods: We performed a post-hoc pooled analysis of data from eight prospective, randomized trials involving serial coronary IVUS. HbA1c was measured at baseline and the average of the follow-up values was taken. The percent atheroma volume (PAV) was calculated as the proportion of the entire vessel wall occupied by atherosclerotic plaque, throughout the segment of interest. Using multivariable mixed modeling, we determined the association of HbA1c with annualized change in PAV. Cox proportional hazard models were used to assess the association of HbA1c with incidence of MACE. Results: Among 2, 791 patients, mean age was 58.9±9 years and 29.1% were women. Mean on-treatment low-density lipoprotein (LDL)-cholesterol was 80.2±33.7 mg/dl and median on-treatment triglycerides (TG) were 125.5 (94.7, 170.2) mg/dl. Mean baseline and follow-up HbA1c was 6.2±1.2% and 6.3±1.2%, respectively. Overall, there was no net significant annualized change in PAV (0.15±0.21, p=0.47). In a fully adjusted multivariable analysis (following adjustment of age, sex, body mass index (BMI), systolic blood pressure, smoking, LDL- and high-density lipoprotein cholesterol, TG levels, peripheral artery disease, trial, region, and baseline PAV), higher on-treatment HbA1c levels were independently associated with annualized changes in PAV [beta-estimate (95% confidence interval): 0.13 (0.07, 0.19), p<0.001]. On-treatment HbA1c levels were significantly and independently associated with incidence of MACE [hazard ratio (95% confidence interval): 1.17 (1.07, 1.28), p<0.001]. Conclusions: Independent of achieved cholesterol levels, vascular risk factors and BMI, greater HbA1c levels significantly associate with coronary atheroma progression and clinical outcomes. These results support the notion of a direct, specific effect of glycemic control upon the natural history of coronary atheroma and atherosclerotic events, supporting the rationale of therapies designed to directly modulate it. FUNDunding Acknowledgement: Type of funding sources: Foundation. Main funding source(s): Iryna Dykun was supported by the German Research Foundation